Effect of Social Media on Nepali Consumer Purchase Decision - Neupane, Rajeswor (Pravaha, 2020)
Social media has significant role on purchasing decision of buyer. The objective of this research paper is to understand how social media network influence on purchasing decision of consumer. A structured, self-administered questionnaire was distributed among 75 people of Baneshwor, Kathmandu. Out of them,60 questionnaire were used for analysis. There was 31 male and 29 female participants. The findings showed that both male and female preferred online services (Face book, YouTube, Instragram, Twitter etc) for social connection. On the basis of result it could be recommended that online marketers should clearly understand the application of social media to promote their products keeping their present consumers as well as attracting more potential customers.